Filling in socio‐ecological knowledge gaps to support marine spatial planning in data‐scarce areas: Example from Zanzibar - Elina A. Virtanen; Niina Käyhkö; Zakaria Khamis; Muhammad Juma Muhammad; Hashim Muumin; Mohammed Habib; Ville Karvinen; Juho Lappalainen; Meri Koskelainen; Niko Kulha; Markku Viitasalo (Conservation Science and Practice)
Abstract Marine spatial planning (MSP) is one of the most important tools for ensuring sustainable use of marine areas. Although MSP is a well‐established method, its adoption in rapidly developing countries is a challenge. One of the main concerns is data adequacy, as the MSP process typically requires a large amount of spatial data on human activities, biodiversity, and socio‐ecological interactions within the planning area. Drawing from an institutional cooperation project in Zanzibar, Tanzania, we share our experience and demonstrate how to fill in socio‐ecological data gaps to support the development of MSP in areas with limited data availability. We developed a rapid and cost‐effective system for collecting biological data, which, together with remote sensing and place‐based participatory mapping, helped formulate the first pilot ecologically informed MSP for Zanzibar. By sharing our results and experiences, we aim to provide best practices, lessons learned, and recommendations for future projects with a similar ecological setting and socio‐economic context.